Unmanageable inequalities: sexism in the film industry. (May 2015) - Jones, Deborah; Pringle, Judith K.
Abstract: This article addresses the question of how gender inequalities are produced in the film industry. In the absence of industry or organizational interventions, these inequalities seem unmanageable. We present an exploration of the gendered working lives of below‐the‐line film workers in New Zealand, in the context of the western film industry. Repeatedly, women activists have pointed out that a perception of gender equity contradicts the statistics, which demonstrate traditional as well as 'new' forms of sexism. In this post‐feminist context inequality is typically invisible and unspoken, and there is a thriving narrative of meritocracy based on talent and determination, where 'you're only as good as your last job'. Below‐the‐line 'crew' are distinguished from creatives in a hierarchy of creativity. In the New Zealand film industry, they are not unionized, and there are no policies addressing gender. From their perspective, their powerlessness in terms of employment rights is taken as a given, a price they pay for doing their dream job. In spite of beliefs about merit, talent and the 'good idea', women's 'good ideas' and their work capabilities across a range of roles are less likely to be recognized and rewarded than those of men.